SISTEM INFORMASI INVENTORY BERBASIS WEBSITE MENGGUNAKAN METODE EXTREME PROGRAMMING (STUDI KASUS: TOKO BANGUNAN PRAYOGA JAYA) - inti, Indra; Deni Muharam; Dwi Sosanto (Jurnal Teknorama (Informatika dan Teknologi El Rahma), 2025)
The Pryoga Jaya Building Shop is a business entity engaged in sales selling building materials and tools which has been established since 2005. The Prayoga Jaya Building Shop is located on Jl. Sukamakmur, District. Ciomas, Bogor Regency, West Java. When monitoring stock of goods, transactions, reports, recording incoming and outgoing goods, everything is still done manually so it can cause human error in monitoring and recording later and makes things easier for the Prayoga Jaya Building Store. In this application, users are divided into two, namely owners and admins, and the method used is Extreme Programming, the Research and Development (R&D) method. The programming language and database that will be used are PHP Native and MySQL. PHP Native ains to provide a solution that is lightweight is able to increase the efficiency of inventory management and minimize errors in recording and processing data. Keywords: Native PHP, Building Store, database, Inventory System, Extreme Programming.